PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN BELI MINUMAN BERKARBONASI BIG COLA - Singgih Santoso; Hardo Caesar Mual (Jurnal Riset Manajemen dan Bisnis, 2013)
The purposes of this study is to test the effect of marketing mix variables (product, price, distribution, and promotion) to Big Cola purchase decision as the dependent variable. Using survey as a data collection method, a questionnaire was distributed to 125 respondents using purposive random sampling method. Data analysis tools are factor analysis and multiple regression analysis. From factor analysis, there is found five factors that influence Big Cola purchasing decisions, while from multiple linear regression analysis obtained result that from four marketing mix variables only distribution variable influence Big Cola purchasing decision. Keywords: marketing mix, factor analysis